2017
DOI: 10.1016/j.ebiom.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable 25(OH)D but Not Total 25(OH)D Is an Independent Determinant for Bone Mineral Density in Chinese Postmenopausal Women

Abstract: Total 25(OH)D levels were determined to assess bone health in elderly populations; however, the bioavailability of 25(OH)D is regulated by the albumin and vitamin D binding protein (DBP) levels and DBP variations. Whether bioavailable 25(OH)D level is a superior biomarker for vitamin D than total 25(OH)D level regarding the BMD and the bone metabolism were not yet fully understood. With a community based cross-sectional study of 967 postmenopausal women, we found that the variant rs7041, but not rs4588, of DBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
5
20
1
Order By: Relevance
“…The conflicting findings can partially be elucidated by ethnic differences in the populations and wider age groups (20–80 years). Additionally, role of bioavailable 25(OH)D but not total 25(OH)D as an independent determinant for BMD is also under debate [ 61 , 62 ] and may be a reason for no association.…”
Section: Discussionmentioning
confidence: 99%
“…The conflicting findings can partially be elucidated by ethnic differences in the populations and wider age groups (20–80 years). Additionally, role of bioavailable 25(OH)D but not total 25(OH)D as an independent determinant for BMD is also under debate [ 61 , 62 ] and may be a reason for no association.…”
Section: Discussionmentioning
confidence: 99%
“…DBP is one of several regulators of serum vitamin D levels, with around 85–90% of the circulating vitamin D pool being bound to DBP [6, 7]. Total vitamin D correlates positively with DBP concentrations [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…These isoforms have different binding affinity for vitamin D [7] as well as different glycosylation patterns [10]. rs4588 and rs7041 have been associated with DBP concentrations [8, 1114] and vitamin D levels [12, 1518] in various populations. Another GC gene variant is the rs2282679 polymorphism, located at the 3’ untranslated region (3′ UTR) of the GC gene, which is involved in the modulation of gene expression and reportedly associated with vitamin D levels [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] A study from China suggested that bioavailable 25(OH)D was a superior biomarker than total 25(OH)D regarding the bone metabolism, and that vitamin D intervention may improve the bone health in elderly populations. 21 This study suggests that we should try to seek the relevance of bioavailable 25(OH)D rather than total 25(OH)D to find its correlation with different parameters.…”
Section: Serum Vitamin D Level In Postmenopausal Womenmentioning
confidence: 99%